(untitled) (Dhaka University Journal of Science, 2015)
The paper considers a class of optimization problems known as extreme point mathematical programming problems. The objective of this paper is to improve the established methods for solving extreme point linear and linear fractional programming problems. To overcome the cumbersome and time consuming procedures of these existing methods, we propose an alternative algorithm to solve such types of problems which is simple and need less computational effort. Two simple examples are given to elucidate our proposed algorithm. Dhaka Univ. J. Sci. 63(2):77-84, 2015 (July)